PERINTAH SUJUD KEPADA ADAM DALAM AL-QUR’AN DAN KANDUNGAN PEDAGOGISNYA: (Sebuah Pendekatan Tafsīr Tarbawī) - Kerwanto Kerwanto (LPPM STAI Nida El-Adabi, 2023)
So far, the interpretation of the Qur'an with an educational approach (tafsīr tarbawī) has not given much attention, even though it is believed that the vital element in the revelation of the Qur'an is education itself. In this article the author attempts to find educational (pedagogical) messages contained in the verses of the Qur'an which discuss the command to prostrate to Adam. This study is important because so far the verses related to this theme have often been associated with theological, Sufistic and political messages (the ideal model of government). While attention to its pedagogical content is still lacking. This study can also be referred to as the thematic interpretation study (tafsīr maudhūi) because the author reviews the content of the verses of the Qur'an based on a particular theme, by following the steps of the thematic method in interpretation. With an educational approach (tarbawī) to the interpretation of these verses, the author finds psychological and ethical messages contained therein. Psychologically, Adam and the Devil as a symbolism of two inherently opposing natures in humans. Therefore, the bad qualities (Satan) must be subordinated to the good qualities (Adam). Meanwhile, ethically, humans can achieve happiness if they are able to subdue the following four bad characters: (1). Being arrogant, (2). Feeling more noble, (3). Kufr against favors and (4). Hasad.